The Effect of Synergistic Compounds on the Susceptibility of Euschistus heros (Hemiptera: Pentatomidae) and Chrysodeixis includens (Lepidoptera: Noctuidae) to Pyrethroids. Issue 2 (8th February 2022) - Boff, Jéssica S; Reis, Alexandre C; Patricia, da S Gubiani; Pretto, Venicius E; Garlet, Cínthia G; Melo, Adriano A; Bernardi, Oderlei
Abstract: The Neotropical brown stink bug, Euschistus heros (F.), and the soybean looper, Chrysodeixis includens (Walker), are key pests of soybean in South America. Low susceptibility to pyrethroids has been reported for both species in Brazil. Here, we evaluate the addition of synergistic compounds piperonyl butoxide (PBO) and diethyl maleate (DEM) to manage E. heros and C. includens with resistance to λ-cyhalothrin and bifenthrin. The LD50 of technical grade and commercial products containing λ-cyhalothrin and bifenthrin decreased against field-collected E. heros exposed to PBO and DEM relative to unexposed insects; synergistic ratios up to 4.75-fold. The mortality also increased when E. heros were exposed to commercial formulations containing λ-cyhalothrin (from 4 to 44%) and bifenthrin (from 44 to 88%) in the presence of synergists. There was also a higher susceptibility of field-collected C. includens to technical grade λ-cyhalothrin when PBO was used; synergistic ratio of 5.50-fold. High lethally of technical grade λ-cyhalothrin was also verified in the presence of PBO, with mortality increasing from 6 to 57%. Our findings indicate the potential utility of synergists in reversing the resistance to λ-cyhalothrin and bifenthrin in E. heros and C. includens and suggest a significant role of metabolic mechanisms underlying the detoxification of both pyrethroids. Graphical Abstract: